2016
DOI: 10.3389/fphar.2016.00243
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Remote Review of Medication Prescriptions for Appropriateness in Pediatric Intensive Care Unit

Abstract: Background: One aspect of ordering and prescribing medication is the requirement for a trained professional to review medication orders or prescriptions for appropriateness. In practice, this review process is usually performed by a clinical pharmacist. However, in many medical centers there is a shortage of staff and a pharmacist is not always available.Objective: To determine whether remote review of medication orders by a pharmacist is a plausible method in a pediatric intensive care unit (PICU).Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
0
0
3
Order By: Relevance
“…When antimicrobial use time and ICU hospitalization time were evaluated, it was found that, in both outcomes, there was a significant reduction in days for patients who had their antimicrobial doses adjusted according to renal function when compared to those who did not have their doses adjusted and/or had inadequate adjustments. Findings consistent with this result have been described in previous studies which reported that the involvement of physicians and pharmacists to ensure appropriate antimicrobial dosage according to renal function was associated with shorter intensive care unit hospitalization times, fewer adverse events and reduced treatment costs 37,38,39,40 .…”
Section: Rbfhsssupporting
confidence: 90%
“…When antimicrobial use time and ICU hospitalization time were evaluated, it was found that, in both outcomes, there was a significant reduction in days for patients who had their antimicrobial doses adjusted according to renal function when compared to those who did not have their doses adjusted and/or had inadequate adjustments. Findings consistent with this result have been described in previous studies which reported that the involvement of physicians and pharmacists to ensure appropriate antimicrobial dosage according to renal function was associated with shorter intensive care unit hospitalization times, fewer adverse events and reduced treatment costs 37,38,39,40 .…”
Section: Rbfhsssupporting
confidence: 90%
“…Nos estudos apresentados pelos artigos A25 e 26, o farmacêutico clínico realizou revisão completa da prescrição de medicamentos do paciente internado em unidade de terapia intensiva, a fim de identificar melhorias e adequações na terapia medicamentosa (BOURNE; CHOO, 2012;LAZARYAN et al, 2016). Ambos os artigos informam que as intervenções clínicas do farmacêutico foram registradas em banco de dados e não mencionam o registro em prontuário do paciente.…”
Section: Unidade De Terapia Intensivaunclassified
“…, 2014); A21(LUO et al, 2017); A22(KHALIL et al, 2018); A23 (PULLINGER; FRANKLIN, 2010); A24(ALSULTAN et al, 2013); A25 (BOURNE; CHOO, 2012); A26(LAZARYAN et al, 2016).…”
unclassified
“…Dentre as estratégias para redução de danos ao paciente, pode ser destacada a atuação do farmacêutico clínico, que por meio de revisões da prescrição e do acompanhamento da farmacoterapia, pode colaborar com a equipe multiprofissional e reduzir os EAM. Um estudo de Lazaryan e cols (2019) demonstrou que as intervenções farmacêuticas relacionadas à correção de dose dos medicamentos têm contribuído para melhorar a segurança do paciente e reduzir o tempo de hospitalização (6). A participação do farmacêutico na correção de dose dos medicamentos excretados por via urinária tem contribuído de forma positiva na função renal do paciente (7).…”
Section: Introductionunclassified